Effect of Quaternary Ammonium Salt Addition to Conventional Biodiesel Production Process - Hussain, Zakir; Meghavathu, Deepa; Kumar, Rakesh (International Journal of Engineering and Technology, 2018)
Biodiesel on a commercial scale is largely produced by transesterification using a conventional homogeneous catalyst like KOH and NaOH. The major problem associated with conventional homogeneous transesterification process is that it is prone to water & FFA content. This problem can be mitigated with some process modification using quaternary ammonium salts. In the present study, the reaction between waste palm oil & methanol was carried in a batch reactor at 65oC & various molar ratios of oil to methanol. Further, the effect of various dosages of tetramethylammonium bromide (TMAB) addition to this reaction was studied. Results show that there is a strong influence of TMAB (a phase transfer catalyst) on the methanol requirement during the reaction and also on the washability characteristics of the produced biodiesel. It was observed that there is a considerable decrease in the molar ratio of methanol to oil requirement during the reaction. Moreover, the addition of TMAB has enhanced the washability of the final biodiesel product by forming less foam. This has a direct advantage of decreasing the water requirement during the purification process.Â